(untitled) (Nuntius Antiquus, 2014)
This paper investigates the presence of tópoi and models of Latin lyric-elegiac poetry in two episodes of Petronius’s Satyricon: the breaking of Encolpius and Giton and the love relationship between Encolpius/ Polyaenus and Circe. In the first episode, the focus will be on the narrator’s poetic inserts, and, in the second one, on prose narrative. We seek to identify and analyse some allusions to lyric-elegiac literary tradition in these episodes, to verify how their presence causes the parody of the models and, in this way, to see how this resource produces a metaliterary discussion. Furthermore, we intend to show that, more than a “mythomaniac narrator” (Conte, 1996), Encolpius presents himself as a literomaniac narrator, assuming various personae throughout the narrative (not only an epic persona, but also a lyric-elegiac one).